COMPARATIVE COMPUTATIONAL STUDIES AND INSILICO IDENTIFICATION OF POLYPROTEIN IN JAPANESE ENCEPHALITIS VIRUS - ABHISHEK KR. MALAKAR; MANISHA MISHRA; ASHISH KR. JAISWAL; PALLAVI (International Journal of Pharma and Bio Sciences, 2011)
Japanese encephalitis virus (JEV) is the major form of viral encephalitis in much of the South-East Asia, India and China. The disease is caused by a mosquito-borne virus known as Japanese encephalitis virus (JEV). The mortality rate in Japanese encephalitis is 30% while 10 - 15% of patients make a full recovery. Japanese encephalitis virus contains a single positive-strand RNA genome nearly 11 kb in length and is not formally thought to generate subgenomic RNA molecules during replication. The envelope (E) polyprotein of JEV interacts with a cellular receptor and mediates membrane fusion to allow viral entry into target cells, thus eliciting neutralizing antibody response. Despite its importance, the three dimensional (3D) structure of polyprotein has not yet been reported. Comparative studies are useful in the prediction of validated 3D structure of a query protein (C5NU03). For the modeling, template protein was obtained by Protein Data Bank (PDB) database, template protein pdb|3I50|chain A having identity (76%) and E value (0.0). From Ramachandran plot analysis it was found that the portion of residues falling into the most favoured regions was (73.0%). These results indicate that the predicted and validated structure (after comparative study) is useful in structure based drug designing, protein-DNA interactions, study of protein-protein interactions, protein-ligand binding and analyzed using other techniques.